2015
DOI: 10.17221/185/2014-swr
|View full text |Cite
|
Sign up to set email alerts
|

Already a short-term soils exposure to the field-rate glufosinate concentration significantly influences soil bacterial communities

Abstract: Kopčáková A., Legáth J., Pristaš P., Javorský P. (2015): Already a short-term soils exposure to the field-rate glufosinate concentration significantly influences soil bacterial communities. Soil & Water Res., 10: 271-277.The early impact of glufosinate derived herbicide Basta ® 15 on bacterial communities of two different soils never exposed to this herbicide was investigated using cultivation approach and non-cultivation based denaturing gradient gel electrophoresis (DGGE) analysis of amplified 16S rRNA genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…There was a trend for considerably more molds and yeasts but less bacteria under flazasulfuron than under the other treatments, however due to high heterogeneity this was not statistically significant. Such unclear patterns of herbicide effects on the microbial soil communities have also been reported by others (Kopčáková et al 2016 ; Newman et al 2016 ). However, a clear difference in soil bacterial and fungal composition in vineyards was reported between herbicide treated and untreated grapevine rows (Chou et al 2018 ; Hendgen et al 2018 ).…”
Section: Resultssupporting
confidence: 71%
“…There was a trend for considerably more molds and yeasts but less bacteria under flazasulfuron than under the other treatments, however due to high heterogeneity this was not statistically significant. Such unclear patterns of herbicide effects on the microbial soil communities have also been reported by others (Kopčáková et al 2016 ; Newman et al 2016 ). However, a clear difference in soil bacterial and fungal composition in vineyards was reported between herbicide treated and untreated grapevine rows (Chou et al 2018 ; Hendgen et al 2018 ).…”
Section: Resultssupporting
confidence: 71%
“…Arable field studies under wheat show that glyphosate-herbicide application caused a shift in the species dominating the arbuscular mycorrhizal fungal community in the rhizosphere, possibly through a modified host plant physiology (Sheng et al 2012 ). In a study where glufosinate-herbicide significantly increased gram-negative bacterial communities, it was suggested that glufosinate might represent an additional carbon source for the soil bacteria (Kopčáková et al 2015 ). Contrastingly, in a rhizobox study following four growth periods, soil bacterial community composition and diversity was less affected by glyphosate-herbicides, although all classes of Proteobacteria increased in relative abundance (Newman et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to examine non-target effects of chemical and mechanical weed control on soil biota and grapevine nutrition. Because earthworms (Gaupp-Berghausen et al 2015 ), mycorrhizal fungi (Zaller et al 2014 ) and also soil microorganisms (Kopčáková et al 2015 ; Aristilde et al 2017 ) have been shown to be affected by chemical herbicides, we hypothesised that herbicide-induced alterations would be evident through changes in plant as well as soil. It has been shown that herbicide use in vineyards affect physiological parameters in the non-target grapevine crop leading a decrease of the leaf dry weight percentage and soluble carbohydrate content with suggested consequences for the berry growth, free amino acid content and an accumulation of ammonium (Saladin et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%